Receptor‐type protein tyrosine phosphatases in cancer. Issue 2 (16th June 2015) - Du, Yu; Grandis, Jennifer R.
Abstract: Protein tyrosine phosphatases (PTPs) play an important role in regulating cell signaling events in coordination with tyrosine kinases to control cell proliferation, apoptosis, survival, migration, and invasion. Receptor‐type protein tyrosine phosphatases (PTPRs) are a subgroup of PTPs that share a transmembrane domain with resulting similarities in function and target specificity. In this review, we summarize genetic and epigenetic alterations including mutation, deletion, amplification, and promoter methylation of PTPRs in cancer and consider the consequences of PTPR alterations in different types of cancers. We also summarize recent developments using PTPRs as prognostic or predictive biomarkers and/or direct targets. Increased understanding of the role of PTPRs in cancer may provide opportunities to improve therapeutic approaches.